Risk of recurrence among patients with HR-positive, HER2-negative, early breast cancer receiving adjuvant endocrine therapy: A systematic review and meta-analysis. (June 2021) - Salvo, Elizabeth M.; Ramirez, Abril Oliva; Cueto, Jenilee; Law, Ernest H.; Situ, Aaron; Cameron, Chris; Samjoo, Imtiaz A.
Abstract: Background: A systematic review and meta-analysis was conducted to assess breast cancer (BC) outcomes among patients with early-stage hormone receptor positive (HR+), human epidermal growth factor receptor 2-negative (HER2-) BC, receiving adjuvant endocrine therapy. Methods: Randomized controlled trials (RCTs) and real-world evidence (RWE) studies were identified using Ovid MEDLINE®, Embase, and Evidence-Based Medicine Reviews. Clinical and methodological similarities including alignment of outcome definitions with standardized definitions for efficacy endpoints criteria were assessed to evaluate feasibility of conducting a meta-analysis. Where feasible, 5-year probabilities of BC recurrence or death were estimated using a Bayesian hierarchical arm-based model. Results: Of 21 included studies, 8 RCTs and 4 RWE studies reported outcome data of interest. There was heterogeneity in outcome reporting, as well as variation in recurrence risk amongst studies with aligned reporting. Of the 12 studies, 10 were considered for inclusion in a meta-analysis of BC recurrence or death. Only a subgroup analysis of node-positive patients (3 studies; n = 7307) was deemed feasible. The 5-year probability of BC recurrence or death was 17.2% (95% credible interval: 14.6%–20.3%). Conclusion: Although studies reporting recurrence outcomes were limited, there remains a high risk of BC recurrence, especially among node-positive patients. Approximately 1 in 6 women with node-positive HR+/HER2- early-stage BC receiving endocrine therapy experience recurrence or death within 5-years of initiating treatment, suggesting a need for novel treatments for this population. Highlights: Recurrence data from RCTs and RWE studies in HR+/HER2- early BC is limited. Recurrence rates for patients receiving endocrine therapy (ET) were summarized. Substantial outcome and clinical heterogeneity between studies was identified. An estimated 1 in 6 patients with node-positive BC may relapse within 5-years. Unmet need exists for therapies to further reduce recurrence in high-risk early BC.